URBAN STRUCTURE OF THE SAN FRANCISCO BAY AREA IN THE CONTEXT OF FORMATION OF A NEW TYPE OF URBAN FABRIC (World Science, 2018)
The purpose of this article is to outline the changes and phenomena within the urban planning structure of the San Francisco bay area, which can be interpreted as impulses associated with the emergence of new post-industrial urban forms. Formation of the theory of impulse modeling of an urban organism requires not only theoretical generalizations and study of the material relating to the peculiarities of the post-industrial (informational) era, but also the search for practical phenomena associated with the rapid development of certain urban areas. At the same time, such development should not be confused with the concept of polycentrism, which was formed during the period of modernism.